2022
DOI: 10.3390/ijerph19052951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychological Distress and Coping Resources on Internet Gaming Disorder: Comparison between Chinese and Japanese University Students

Abstract: The high prevalence of Internet gaming disorder (IGD) among Asian youth indicates an urgent need to identify protective factors and examine their consistency across Asian cultures in order to facilitate cost-effective interventions. Based on the transactional theory of stress and coping, this study collected data of 1243 online gamers (45% males; 18–25 years) through an anonymous survey from universities in China and Japan and investigated whether three coping resources (i.e., mindfulness, coping flexibility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…This scale has been applied to various clinical and non-clinical populations in many countries ( Beaufort, De Weert-Van Oene, Buwalda, de Leeuw, & Goudriaan, 2017 ; Bibi, Lin, Zhang, & Margraf, 2020 ; Lee, Lee, & Moon, 2019 ). The Chinese version has also been widely used across populations, including young adults (e.g., Chen, Yu, Su, Tong, & Wu, 2021 ; Lu et al., 2018 ; Wu et al., 2022 ). The depression subscale of DASS-21 showed high internal consistency and good criterion validity (for a review, Lee et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…This scale has been applied to various clinical and non-clinical populations in many countries ( Beaufort, De Weert-Van Oene, Buwalda, de Leeuw, & Goudriaan, 2017 ; Bibi, Lin, Zhang, & Margraf, 2020 ; Lee, Lee, & Moon, 2019 ). The Chinese version has also been widely used across populations, including young adults (e.g., Chen, Yu, Su, Tong, & Wu, 2021 ; Lu et al., 2018 ; Wu et al., 2022 ). The depression subscale of DASS-21 showed high internal consistency and good criterion validity (for a review, Lee et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“… 38 Therefore, as a crucial buffer resource, social support can not only alleviate the burnout caused by the imbalance of individual resource allocation, but also help individual avoid problematic Internet behaviors. 39 A meta-analysis also provided direct evidence of the negative association between social support and MPD. 40 An empirical survey of adolescents in Poland has also shown that social support is an important resource for avoiding MPD.…”
Section: Introductionmentioning
confidence: 97%
“…According to a recent meta-analysis, one in every three IGD patients experienced depression [ 17 ]. Japanese students tend to have a high risk of IGD and physiological stress [ 18 ]. Furthermore, more people in Asian countries are showing behaviors associated with gaming disorder and online addiction amid the coronavirus (COVID-19) pandemic [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%